Quaternized and Unmodified Chitosans: Hydrodynamic Properties - Yevlampieva, N.P.; Gubarev, A.S.; Gorshkova, M. Yu.; Okrugin, B.M.; Ryumtsev, E.I. (Journal of Research Updates in Polymer Science, 2015)
Molecular properties of N-[(2-hydroxy-3-trimethylammonium)propyl]chitosan (modified chitosan) series with the averaged quaternization degree 90% have been studied in comparison with the unmodified chitosan series by the method of translation isothermal diffusion, viscometry and static light scattering in dilute solutions in 0.33М СН3СООН+0.2М CH3СООNa at pH 3.54. Molecular mass, translation diffusion coefficient, and hydrodynamic size of the homologues samples in the modified/unnmodified series have been determined as well as their chain rigidity and Mark-Kuhn-Houwink equations at acidic pH. It was established that the size of modified chitosan molecules might be smaller than the initial polysaccharide of an equal polymerization degree in the same solvent, which was explained by the change of thermodynamic conditions and the change of the ratio of thermodynamic/electrostatic contributions to the total chain rigidity. Quaternized chitosan molecules displayed the different hydrodynamic behavior in 0.33М СН3СООН+0.2М CH3СООNa and in 0.2M NaCl (neutral pH). Solution properties of quaternized chitosan at neutral pH had been identified as the concentration dependent. The threshold influence of the secondary amino group protonation on the hydrodynamic properties of modified chitosan molecules was detected in 0.2M NaCl at the solute concentration range 0.001-0.004 g/cm3.